2020
DOI: 10.1002/ldr.3554
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of future climate and land use change on water yield in a semiarid basin in Iran

Abstract: Studying the interaction between hydrology, land use, and climate change is necessary to support sustainable water resources management. It is unknown how land management interventions in dry climate conditions can benefit water yield in the context of climate and land use change interactions. In this study, we assessed the effects of both land use and predicted climate change on the Mordagh Chay basin water yield using the Integrated Valuation of Ecosystem Services and Tradeoffs model. First, we modeled the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Although the findings emphasize the driving effect of precipitation, the contribution of other factors such as actual evapotranspiration to spatial differentiation of water yield cannot be denied. Similarly, Shirmohammadi found that the prediction result on the future water yield in the Urmia lake region was mainly sensitive to precipitation and evapotranspiration, especially precipitation [16]. Therefore, predicting the change of precipitation can be used to reveal the variation trend of water yield.…”
Section: Drivers Of Changes In Ecosystem Servicesmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the findings emphasize the driving effect of precipitation, the contribution of other factors such as actual evapotranspiration to spatial differentiation of water yield cannot be denied. Similarly, Shirmohammadi found that the prediction result on the future water yield in the Urmia lake region was mainly sensitive to precipitation and evapotranspiration, especially precipitation [16]. Therefore, predicting the change of precipitation can be used to reveal the variation trend of water yield.…”
Section: Drivers Of Changes In Ecosystem Servicesmentioning
confidence: 97%
“…Under the combined action of natural factors and human activities, ecosystem services showed significant spatial differences. The main factors affecting ecosystem services are climate factors and land use factors [16,66]. In terms of spatial distribution, water yield is closely related to precipitation and actual evapotranspiration.…”
Section: Drivers Of Changes In Ecosystem Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The water yield module of the InVEST model, according to the water balance formula, ignores the interactive flow between the surface and groundwater and subtracts the annual actual evapotranspiration from the annual precipitation to obtain the regional annual water yield. At the same time, the model determines the contribution of each landscape to the water yield (Shirmohammadi et al 2020):…”
Section: Calculating Water Yield In the Invest Modelmentioning
confidence: 99%